When Mixed Layers Are Not Mixed. Storm‐Driven Mixing and Bio‐optical Vertical Gradients in Mixed Layers of the Southern Ocean. Issue 10 (15th October 2018) - Carranza, Magdalena M.; Gille, Sarah T.; Franks, Peter J. S.; Johnson, Kenneth S.; Pinkel, Robert; Girton, James B.
Abstract: Mixed layers are defined to have homogeneous density, temperature, and salinity. However, bio‐optical profiles may not always be fully homogenized within the mixed layer. The relative timescales of mixing and biological processes determine whether bio‐optical gradients can form within a uniform density mixed layer. Vertical profiles of bio‐optical measurements from biogeochemical Argo floats and elephant seal tags in the Southern Ocean are used to assess biological structure in the upper ocean. Within the hydrographically defined mixed layer, the profiles show significant vertical variance in chlorophyll‐a (Chl‐a) fluorescence and particle optical backscatter. Biological structure is assessed by fitting Chl‐a fluorescence and particle backscatter profiles to functional forms (i.e., Gaussian, sigmoid, exponential, and their combinations). In the Southern Ocean, which characteristically has deep mixed layers, only 40% of nighttime bio‐optical profiles were characterized by a sigmoid, indicating a well‐mixed surface layer. Of the remaining 60% that showed structure, ∼40% had a deep fluorescence maximum below 20‐m depth that correlated with particle backscatter. Furthermore, a significant fraction of these deep fluorescence maxima were found within the mixed layer (20–80%, depending on mixed‐layer depth definition and season). Results suggest that the timescale between mixing events that homogenize the surface layer is often longer than biological timescales of restratification. We hypothesize that periods of quiescence between synoptic storms, which we estimate to be ∼3–5 days (depending on season), allow bio‐optical gradients to develop within mixed layers that remain homogeneous in density. Plain Language Summary: Storms influence high‐latitude oceans by stirring the upper ocean nearly continuously. This wind mixing is usually expected to homogenize properties within the upper layer of the ocean, known as the mixed layer. New water column observations from floats and elephant seal tag confirm homogenization of hydrographic properties that determine density of seawater (e.g., temperature and salinity); however, biogeochemical properties are not necessarily homogenized. Most of the time optical measurements of biological properties within the mixed layer show vertical structure, which is indicative of phytoplankton biomass. These vertical inhomogenities are ubiquitous throughout the Southern Ocean and may occur in all seasons, often close to the base of the mixed layer. Within the mixed layer, observations suggest that biological processes create inhomogenities faster than mixing can homogenize. We hypothesize that 3‐ to 5‐day periods of quiescence between storm events are long enough to allow bio‐optical structure to develop without perturbing the mixed layers' uniform density. This may imply that phytoplankton in the Southern Ocean are better adapted to the harsh environmental conditions than commonly thought. Key Points: Chl‐a fluorescence and particle backscatter show significant vertical gradients within hydrographically defined mixed layers Between 20% and 80% of nighttime deep Chl‐a fluorescence maxima are found within the mixed layer Bio‐optical vertical structure appears to be linked to storm‐mixing events